S-Adenosyl methionine synthetase 1 limits fat storage in Caenorhabditis elegans - Ehmke, Madeleine (Springer Berlin Heidelberg, 2014)
Cytosolic lipid droplets are versatile, evolutionarily conserved organelles that are important for the storage and utilization of lipids in almost all cell types. To obtain insight into the physiological importance of lipid droplet size, we isolated and characterized a new S-adenosyl methionine synthetase 1 (SAMS-1)-deficient Caenorhabditis elegans mutant, which have enlarged lipid droplets throughout its life cycle. We found that the sams-1 mutant showed a markedly reduced body size and progeny number; impaired synthesis of phosphatidylcholine, a major membrane phospholipid; and elevated expression of key lipogenic genes, such as dgat-2, resulting in the accumulation of triacylglyceride in fewer, but larger, lipid droplets. The sams-1 mutant store more than 50 % (wild type: 10 %) of its intestinal fat in large lipid droplets, ≥10 μm(3) in size. In response to starvation, SAMS-1 deficiency causes reduced depletion of a subset of lipid droplets located in the anterior intestine. Given the importance of liberation of fatty acids from lipid droplets, we propose that the physiological function of SAMS-1, a highly conserved enzyme involved in one-carbon metabolism, is the limitation of fat storage to ensure proper growth and reproduction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12263-014-0386-6) contains supplementary material, which is available to authorized users.